Specific combinations of biallelic POLR3A variants cause Wiedemann-Rautenstrauch syndrome. Issue 12 (15th October 2018) - Paolacci, Stefano; Li, Yun; Agolini, Emanuele; Bellacchio, Emanuele; Arboleda-Bustos, Carlos E; Carrero, Dido; Bertola, Debora; Al-Gazali, Lihadh; Alders, Mariel; Altmüller, Janine; Arboleda, Gonzalo; Beleggia, Filippo; et al.
Abstract : Background: Wiedemann-Rautenstrauch syndrome (WRS) is a form of segmental progeria presenting neonatally, characterised by growth retardation, sparse scalp hair, generalised lipodystrophy with characteristic local fatty tissue accumulations and unusual face. We aimed to understand its molecular cause. Methods: We performed exome sequencing in two families, targeted sequencing in 10 other families and performed in silico modelling studies and transcript processing analyses to explore the structural and functional consequences of the identified variants. Results: Biallelic POLR3A variants were identified in eight affected individuals and monoallelic variants of the same gene in four other individuals. In the latter, lack of genetic material precluded further analyses. Multiple variants were found to affect POLR3A transcript processing and were mostly located in deep intronic regions, making clinical suspicion fundamental to detection. While biallelic POLR3A variants have been previously reported in 4H syndrome and adolescent-onset progressive spastic ataxia, recurrent haplotypes specifically occurring in individuals with WRS were detected. All WRS-associated POLR3A amino acid changes were predicted to perturb substantially POLR3A structure/function. Conclusion: Biallelic mutations in POLR3A, which encodes for the largest subunit of the DNA-dependent RNA polymerase III, underlie WRS. No isolated functional sites in POLR3A explain the phenotype variability in POLR3A-related disorders. We suggest that specific combinations of compound heterozygous variants must be present to cause the WRS phenotype. Our findings expand the molecular mechanisms contributing to progeroid disorders.